2009
DOI: 10.1254/jphs.08238fp
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms Underlying Statin-Induced Skeletal Muscle Toxicity in L6 Fibroblasts and in Rats

Abstract: Abstract. 3-Hydroxy-3-methylglutaryl CoA reductase inhibitors (statins) are safe and welltolerated therapeutic drugs. However, they occasionally induce myotoxicity such as myopathy and rhabdomyolysis. Here, we investigated the mechanism of statin-induced myotoxicity in L6 fibroblasts and in rats in vivo. L6 fibroblasts were differentiated and then treated with pravastatin, simvastatin, or fluvastatin for 72 h. Hydrophobic simvastatin and fluvastatin decreased cell viability in a dose-dependent manner via apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 19 publications
4
34
0
5
Order By: Relevance
“…2). One group using rat immortalized L6 myoblasts reported that the depletion of FPP is critical for myotoxicity (22), but another laboratory using the same cell line suggested that GGPP was the critical isoprenoid (12). In our hands, it was not FPP (3 mM), but GGPP (3 mM) alone, because the addition of GGPP, not FPP, in the presence of fluvastatin completely canceled the toxic effects of statins in skeletal myofibers (15,17).…”
Section: Depletion Of Geranylgeranylpyrophosphate Triggers Statin Myomentioning
confidence: 62%
See 2 more Smart Citations
“…2). One group using rat immortalized L6 myoblasts reported that the depletion of FPP is critical for myotoxicity (22), but another laboratory using the same cell line suggested that GGPP was the critical isoprenoid (12). In our hands, it was not FPP (3 mM), but GGPP (3 mM) alone, because the addition of GGPP, not FPP, in the presence of fluvastatin completely canceled the toxic effects of statins in skeletal myofibers (15,17).…”
Section: Depletion Of Geranylgeranylpyrophosphate Triggers Statin Myomentioning
confidence: 62%
“…This discrepancy was more prominent in the case of hydrophilic statins. Although 5-mM serum concentration of pravastatin damaged the skeletal muscle in an animal (rat) experiment, this concentration and a concentration even as high as 1 mM did not cause cell death in cultured rat skeletal myofibers (11,12). Therefore, it seemed inappropriate to analyze the adverse effects of statins using cultured myoblasts.…”
Section: In Vitro Skeletal Muscle Models For Statins Myotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, fluvastatin could partially reverse the impairment of both contractile and diastolic functions in a dose-independent manner; however, the middle dose rather than the high dose of fluvastatin was significantly more effective in improving cardiac function in the DM rats. The DM+FH rats suffered severe rhabdomyolysis-toxicity of the skeletal muscle due to RhoA dysfunction following the loss of lipid modification with geranylgeranyl pyrophos phate [23,24] . Consequently, it was reasonable to presume that pain caused by severe rhabdomyolysis may contribute to the negative impact on cardiac function seen in the DM+FH rats.…”
Section: Discussionmentioning
confidence: 99%
“…12 This is highlighted by the findings that supplementation of geranylgeranylpyrophosphate to cultured skeletal myotubes or isolated myofibers treated with statins leads to attenuation of toxicity, 11,13-15 whereas inactivation of a Rab and RhoA induces toxicity. 11,13 Decreased geranylgeranylation of small GT- …”
mentioning
confidence: 99%